2010
DOI: 10.1016/j.phymed.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity of lichen substances

Abstract: We describe here the extraction and identification of several classes of phenolic compounds from the lichens Parmotrema dilatatum (Vain.) Hale, Parmotrema tinctorum (Nyl.) Hale, Pseudoparmelia sphaerospora (Nyl.) Hale and Usnea subcavata (Motyka) and determined their anti-tubercular activity. The depsides (atranorin, diffractaic and lecanoric acids), depsidones (protocetraric, salazinic, hypostictic and norstictic acids), xanthones (lichexanthone and secalonic acid), and usnic acid, as well seven orsellinic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 16 publications
2
61
1
2
Order By: Relevance
“…Thanks to the presence of different extracts, this phytogel can find a potential application in a variety of skin diseases such as acne and eczema (due to the presence of the horsetail extract) [27], skin inflammation, wounds, purulent processes (due to the presence of the yarrow extract) [47], skin burns and wound infections (due to the presence of H. perforatum extract) [19], skin regeneration [48] and a antirheumatic agent (S. officinale extract) [49]. Usnic acid and its salts have well known antioxidant and antimicrobial properties [29,30], so Na-usniate is also an important component of the investigated phytogel in terms of the antioxidant and antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the presence of different extracts, this phytogel can find a potential application in a variety of skin diseases such as acne and eczema (due to the presence of the horsetail extract) [27], skin inflammation, wounds, purulent processes (due to the presence of the yarrow extract) [47], skin burns and wound infections (due to the presence of H. perforatum extract) [19], skin regeneration [48] and a antirheumatic agent (S. officinale extract) [49]. Usnic acid and its salts have well known antioxidant and antimicrobial properties [29,30], so Na-usniate is also an important component of the investigated phytogel in terms of the antioxidant and antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The antimicrobial and antioxidant activities of these plant extracts were tested before [1,[25][26][27][28], as well as the antimicrobial and antioxidant activities of usnic acid and related compounds from lichens [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Ingólfsdóttir et al (1998) reported that salazinic acid develops antimycobacterial activity. Honda et al (2010) studied the antibiotic properties of several different depsidones, protocetraric, salazinic, norstictic, hypostictic acids, and five salazinic acid derivatives on Mycobacterium tuberculosis. They conclude that the activity against the microorganism depends on the physico-chemical parameters (lipophilicity and pKa) of each compound, that is a function of the substituents in each molecule evaluated and of its structural characteristics.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…It also acts as an insecticide, moisturizer, antihistamine, and agent that offers protection from the harmful effects of lightning UV (Fournet et al 1997, Cochietto et al 2002, Ingólfsdóttir 2002, Falcão et al 2004, Ribeiro et al 2006, Honda et al 2010. In humans, a hepatotoxic effect was observed when it was used systemically (Moura et al 2008).…”
Section: Introductionmentioning
confidence: 99%